Vehicle Taxpayer Compliance And The Implementation Of The Two-Wheeled Vehicle Tax Amnesty Program In Cirebon Regency - Mutiara Triani; Siti Khumayah; Kacung Arif Rohman (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the implementation of the two wheeled vehicle tax amnesty program and its implications for taxpayer compliance in Cirebon Regency. An empirical qualitative approach grounded in a descriptive post positivist perspective was employed to explore policy implementation, taxpayer responses, and long term compliance challenges. Data were collected through in depth interviews, field observations, and documentary analysis involving Samsat officials and motorcycle taxpayers. The findings indicate that the program was implemented effectively through structured administrative procedures, institutional coordination, service adaptation, and public outreach mechanisms. The program contributed to increased tax payment participation, settlement of tax arrears, and improved taxpayer responsiveness during the amnesty period. Evidence also demonstrates a decline in inactive vehicle tax records and a temporary improvement in compliance behavior. Despite these positive outcomes, the sustainability of compliance remains uncertain because a portion of taxpayers continued to rely on incentive based policies and displayed a tendency to postpone obligations while anticipating future amnesty programs. Long term compliance appears to depend on stronger taxpayer awareness, moral obligation, digital governance, and continuous institutional engagement. The study highlights the importance of integrating policy effectiveness with sustainable behavioral transformation to strengthen regional tax administration and support long term revenue performance.